PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAMES-TOURNAMENT MODEL MONOPOLI BERBASIS KARAKTER UNTUK MENINGKATKAN PRESTASI BELAJAR FISIKA (UPEJ Unnes Physics Education Journal, 2015)
This study aims to determine whether the type of cooperative learning-games-tournament teams monopoly character-based models can improve learning achievement through a set of game physics are applied to the experimental class students. The research was conducted in SMP Negeri 1 Lemahabang Cirebon academic year 2014/2015. This study uses a learning model independent variables and the dependent variable learning achievement. This study used a test to determine the magnitude of improvement Gain the ability of students in the experimental class before and after a given treatment, and a t-test to determine whether the cognitive learning experiment class is greater than the control class. The results showed an average of cognitive learning achievement of students in the control class of 50.3 and 60.5 in the experimental class with a gain factor of 0.61. By significance was calculated using the t test with significance level of 5% the result is 2.35, so we concluded that students experienced a significant increase in achievement. On average affective learning achievement experimental class of 85 and control class is 69. The average score psychomotor learning achievement in the experimental class of 74 and the control class is 57. Based on the results obtained it can be concluded that cooperative learning-games-tournament teams monopoly character-based models can improve learning achievement of physics in the cognitive domain.